2017
DOI: 10.1016/j.exger.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress affects mortality rate more than social behavior, gene expression or oxidative damage in honey bee workers

Abstract: Early life stressors can affect aging and life expectancy in positive or negative ways. Individuals can adjust their behavior and molecular physiology based on early life experiences but relatively few studies have connected such mechanisms to demographic patterns in social organisms. Sociality buffers individuals from environmental influences and it is unclear how much early life stress affects later life history. Workers of the honey bee (Apis mellifera L.) were exposed to two stressors, Varroa parasitism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
1
6
0
1
Order By: Relevance
“…Interestingly, exposure to thiamethoxam (0.25 ng or 1.00 ng) as a single stressor did not affect bee survival at all, but mortality was increased in bees injected with DWV alone or coexposed to DWV and 0.25 ng of thiamethoxam. These results correspond with previous studies showing that DWV has a deleterious effect on honey bee lifespan (Woyciechowski and Moroń, 2009;Dainat et al, 2012;Martin et al, 2013;Benaets et al, 2017;Rueppell et al, 2017). Notably, by using a Radio-Frequency Identification device, Benaets et al (2017) found that experimentally DWV infected bees had a greater earlylife mortality (up to 81%) as compared to control bees (up to 67%), and Martin et al (2013) observed a high decrease in longevity of adults that were parasitized by varroa during the larvae/pupae stages.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, exposure to thiamethoxam (0.25 ng or 1.00 ng) as a single stressor did not affect bee survival at all, but mortality was increased in bees injected with DWV alone or coexposed to DWV and 0.25 ng of thiamethoxam. These results correspond with previous studies showing that DWV has a deleterious effect on honey bee lifespan (Woyciechowski and Moroń, 2009;Dainat et al, 2012;Martin et al, 2013;Benaets et al, 2017;Rueppell et al, 2017). Notably, by using a Radio-Frequency Identification device, Benaets et al (2017) found that experimentally DWV infected bees had a greater earlylife mortality (up to 81%) as compared to control bees (up to 67%), and Martin et al (2013) observed a high decrease in longevity of adults that were parasitized by varroa during the larvae/pupae stages.…”
Section: Discussionsupporting
confidence: 89%
“…Overt infections often occur when the virus is transmitted to the pupae by the Varroa destructor mite through injection while the mite feeds (de Miranda and Genersch, 2010;Möckel et al, 2011), causing deformed wings. In addition, DWV infection is known to impair associative learning and memory formation (Iqbal and Mueller, 2007), weaken flight ability (Wells et al, 2016), induce precocious foraging trips (Benaets et al, 2017) and drastically reduce bee lifespan (Rueppell et al, 2017). Thiamethoxam is a neonicotinoid insecticide commonly used around the world (Sanchez-Bayo, 2014), especially on rapeseed oil, a crop that is widespread and attractive to honey bees (Simon-Delso et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Lasius niger queens invest in DNA and protein repair rather than antioxidants ( Lucas et al, 2016 ). Oxidative damage can also be induced by stressful environmental conditions in honeybees ( Simone-Finstrom et al, 2016 ), but does not necessarily result from lifespan reducing stress ( Rueppell et al, 2017 ). In the reproductively plastic termite Crypotermes secundus , colonies maintained at constant temperature counterintuitively showed higher stress responses, lower survival, and reduced reproductive output than those at variable temperatures ( Rau and Korb, 2021 ).…”
Section: Antioxidants and Aging In Eusocial Speciesmentioning
confidence: 99%
“…Each sample was run in technical triplicates for target genes and reference gene actin by means of the deltadelta Ct method (Wang et al 2012). Studies have shown that actin is one of the most stable gene expressed across different stages, tissues, and under stress condition (Lourenco et al 2008;Scharlaken et al 2008) and is often used as a single reference gene for expression studies in honey bee (Alaux et al 2012;Ihle et al 2015;Rueppell et al 2017;Li et al 2018). One sample was lost during the procedures, leading to the final sample sizes of N(urse) control = 16, N LPS = 15, N PGN = 16, F(orager) control = 16, F LPS = 16, and F PGN = 16.…”
Section: Quantitative Real-time Pcr Analysesmentioning
confidence: 99%